Analysis of Performance Appraisal Systems Used in the Manufacturing Industries of Punjab - Khosla, Rajiv; Saini, Ramandeep (Prabandhan: Indian Journal of Management, 2015)
Achievement of organizational goals primarily calls for an effective utilization of human resources besides other resources. Pertinently, organizational goals can be achieved by taking into consideration the nature, abilities, and limitations of the manpower, enabling them to actualize their full potential, utilizing them fully for the growth of the organization, maintaining their quality, and integrating them with other resources. The performance appraisal system is a system of eliciting feedback, benchmarking it, communicating the same to the employees to bring holistic development in them besides evaluating the potential of employees. The present study aimed to analyze the performance appraisal system being practiced in industries of Punjab besides identifying the factors affecting the same.